Plant community assembly is jointly shaped by environmental and dispersal filtering along elevation gradients in a semiarid area, China - Zheng, Jie; Arif, Muhammad; He, Xinrui; Ding, Dongdong; Zhang, Songlin; Ni, Xilu; Li, Changxiao (Frontiers in Plant Science, 2022)
Environmental filtering (EF) and dispersal filtering (DF) are widely known to shape plant community assembly. Particularly in arid and semi-arid mountainous regions, however, it remains unclear whether EF or DF dominate in the community assembly of different life forms or how they interact along elevational gradients. This research aims to reveal how different ecological processes influence herbaceous and woody community assembly and how they respond to various environmental drivers and elevational gradients. Here we integrated taxonomic diversity (TD), phylogenetic diversity (PD), and ecological drivers across an elevational gradient of 1,420 m in the Helan Mountain Nature Reserve, in typical arid and semi-arid areas of China. This study showed that the TD and PD of herbaceous communities significantly increase linearly with changing elevation gradients, while woody 'TD' showed a unimodal pattern, and there was little relationship between woody 'PD' and elevation. Herbaceous species exhibited significant phylogenetic clustering at low elevations, where they were influenced by climate, aspect, and tree cover. However, woody species exhibited random patterns across elevations. Herbaceous and woody species' taxonomic and phylogenetic beta diversity is governed primarily by spatial turnover rather than nestedness. Spatial turnover is caused primarily by EF and DF's combined influence, but their relative importance differs between herbaceous and woody communities. Therefore, we conclude that the responses of herbaceous and woody plants along elevation gradients in the Helan Mountains are decoupled due to their different adaptation strategies to climate factors in the drylands. These findings are important for understanding the assembly mechanisms driving plant communities in dryland under the context of dramatic increases in drought driven by climate warming.